2019
DOI: 10.5812/ijpbs.74234
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Amphetamine and Methamphetamine Use Among Clients of Opioid Maintenance Treatment Programs in Golestan, Iran

Abstract: Background: Concurrent use of stimulants during opioid maintenance treatments (OMTs) negatively impacts the treatment outcomes. Objectives: The aim of this study is to evaluate the prevalence and correlation of amphetamine and methamphetamine use among OMT clients in Golestan province-Northeast of Iran. Methods: In a cross-sectional study, 750 OMT clients were recruited through a two-stage cluster sampling. Face-to-face interviews were conducted to complete the study questionnaire. Urine samples were also take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…Although the observed pattern may be simply due to possible biases in selection of sample, it might also be due to the recent shift in substance use practices among PWID in Iran and the increase in poly-drug use involving nonopioids among PWID in Iran. Recent studies have shown that methamphetamine use has been increasing among PWID with opioid use disorder [20]. We also found that compared to PWID who used only opioids within the last month, those who used only non-opioids and those who used opioids and non-opioids simultaneously were less likely to have received OAT.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Although the observed pattern may be simply due to possible biases in selection of sample, it might also be due to the recent shift in substance use practices among PWID in Iran and the increase in poly-drug use involving nonopioids among PWID in Iran. Recent studies have shown that methamphetamine use has been increasing among PWID with opioid use disorder [20]. We also found that compared to PWID who used only opioids within the last month, those who used only non-opioids and those who used opioids and non-opioids simultaneously were less likely to have received OAT.…”
Section: Discussionsupporting
confidence: 50%
“…On the other hand, the use of methamphetamine in PWID reduces the effectiveness of OAT program and subsequently lower satisfaction of patients from OAT [22]. These issues are problematic in a way that treatment of PWID who use synthetic drugs has turned into a challenging issue within the last years [20,21]. In Iran, there are only a limited number of centers providing treatments for stimulant use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Although the observed pattern may be simply due to possible biases in selection of the participants, it might also be due to the recent shift in substance use practices among PWID in Iran and the increase in poly-drug use involving non-opioids among them. Recent studies have shown that methamphetamine use has been *P values are for comparison of prevalence between two rounds of surveys in 2010 and 2014 **Type of substance: non-opioids = Shishe, hashish/grass/cannabis, marijuana, ecstasy, cocaine, and methamphetamine/crystal; opioids = opium, opium sap, opium syrup, heroin, norchizak, tamchizak, buprenorphine, methadone, and crack increasing among PWID with opioid use disorder [20]. We also found that compared to PWID who used only opioids within the previous month, those who used only non-opioids and those who used opioids and non-opioids simultaneously, were less likely to have received OAT.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of methamphetamine in PWID reduces the effectiveness of OAT programs and subsequently leads to lower satisfaction of patients with OAT [22]. These issues are problematic in a way that treatment of PWID who use synthetic drugs has turned into a challenging issue within the last few years [20,21]. In Iran, there are only a limited number of centers providing treatments for stimulant use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors highlighted that positive urine specimens for morphine were significantly higher among those who had positive urine samples for amphetamines. Furthermore, lifetime alcohol use and imprisonment were associated with positive urine samples for amphetamines (1). Recently, at the research level, psychological treatments such as motivational interviewing, the Matrix model, and cognitive-behavioral therapy have been evaluated for stimulant users in OMTPs (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%